A case report of simultaneous orthotopic liver transplantation and jejunectomy. Issue 1 (December 2016) - Chen, Guoyong; Wei, Sidong; Zou, Zhongwu; Sun, Jianjun; Tang, Gaofeng; Chen, Jianbin; Zhou, Shaotang
Abstract Background Liver transplantation (LT) accompanied by jejunectomy to treat patients with acute or chronic hepatic cirrhosis with thrombosis in the portal system is extremely rare. Case presentation A 47-year-old man presented with hematemesis and melena, and a diagnosis of decompensated cirrhosis, chronic portal vein thrombosis (PVT) and secondary gastro-esophageal variceal hemorrhage was made. Coagulants were administered, but portal vein thrombi occurred rapidly, and gastrointestinal bleeding recurred shortly thereafter. The patient underwent LT, phlebothrombectomy and a partial jejunectomy. His recovery from a fistula was uneventful, and follow-up visits over 70 months were unremarkable. Conclusion Liver transplantation and partial jejunectomy is a feasible and effective surgical option for select patients with end-stage liver disease accompanied by acute portal venous thrombosis.